Pengaruh Konten TikTok @bts_official_bighit terhadap Keputusan Pembelian Photocard - Patricia, Theresa; Junaidi, Ahmad (Kiwari, 2024)
Social media is one of human's best friends who always accompanies almost all times and places. Almost all aspects of life can be accessed by and from social media. Nowadays, we don't need the hassle and difficulty of interacting and shopping to entertain ourselves. There are platforms and applications that can fulfill this, for example TikTok. TikTok has a big influence in various content, one of which is in the K-Pop field. This research aims to prove how much media exposure, TikTok @bts_official_bighit content has on purchasing decisions for women aged 18-25 years in Jakarta. In this research, the author uses the S-O-R theory and media exposure, with the hope and perspective that when an organism is given a stimulus, it will cause a response. The research method used is quantitative with a non-probability sampling method with a purposive sampling technique the sample used was 142 respondents distributed randomly online to writer’s friends. The T test outcomes indicate that the independent variable exhibits a t-value of 12.354, accompanied by a p-value of 0.000. Consequently, it can be inferred that the TikTok account content variable significantly (partially) impacts the decision to purchase photocard items. The coefficient of determination results reveal that the content from the TikTok account @bts_official_bighit contributes 52.2% to the variability in purchasing decisions for photocards among women aged 18-25 years in Jakarta. The remaining 47.8% is attributed to factors beyond the scope of the model. Media sosial merupakan salah satu sahabat manusia yang selalu menemani hampir di seluruh waktu dan tempat. Ada platform dan aplikasi yang dapat memenuhi hal tersebut contohnya TikTok. TikTok membawa pengaruh besar dalam berbagai konten, salah satunya di bidang K-Pop. Penelitian ini bertujuan untuk membuktikan seberapa besar terpaan media, konten TikTok @bts_official_bighit terhadap keputusan pembelian pada wanita berusia 18-25 tahun di Jakarta. Pada penelitian ini, penulis menggunakan teori S-O-R dan terpaan media, dengan harapan dan perspektif bahwa ketika organisme diberikan stimulus, maka akan menimbulkan respon. Metode penelitian yang digunakan adalah kuantitatif dengan metode non-probability sampling dengan teknik purposive sampling. Hasil uji T menyatakan bahwa variabel independen memiliki nilai t sebesar 12,354, disertai dengan nilai p sebesar 0,000. Maka karena itu, ditarik kesimpulan bahwa variabel konten akun TikTok secara signifikan (sebagian) berpengaruh pada keputusan untuk membeli kartu foto. Hasil koefisien determinasi menunjukkan bahwa konten dari akun TikTok @bts_official_bighit memberikan kontribusi sebesar 52,2% terhadap variabilitas dalam keputusan pembelian photocard oleh wanita berusia 18-25 tahun di Jakarta. Di samping itu, 47,8% sisanya dijelaskan oleh faktor-faktor di luar lingkup model.